Postnatal Changes in Humerus Cortical Bone Thickness Reflect the Development of Metabolic Bone Disease in Preterm Infants - Tokuriki, Shuko (Dis Markers, 2016)
Objective. To use cortical bone thickness (CBT) of the humerus to identify risk factors for the development of metabolic bone disease in preterm infants. Methods. Twenty-seven infants born at <32 weeks of gestational age, with a birth weight of <1,500 g, were enrolled. Humeral CBT was measured from chest radiographs at birth and at 27-28, 31-32, and 36–44 weeks of postmenstrual age (PMA). The risk factors for the development of osteomalacia were statistically analyzed. Results. The humeral CBT at 36–44 weeks of PMA was positively correlated with gestational age and birth weight and negatively correlated with the duration of mechanical ventilation. CBT increased with PMA, except in six very early preterm infants in whom it decreased. Based on logistic regression analysis, gestational age and duration of mechanical ventilation were identified as risk factors for cortical bone thinning. Conclusions. Humeral CBT may serve as a radiologic marker of metabolic bone disease at 36–44 weeks of PMA in preterm infants. Cortical bones of extremely preterm infants are fragile, even when age is corrected for term, and require extreme care to lower the risk of fractures.